1994
DOI: 10.1007/bf00294400
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of acute variceal hemorrhage

Abstract: The advent of more effective nonoperative therapies, mainly endoscopic variceal sclerosis, has decreased the need for emergency surgery for control of acute variceal hemorrhage. In centers where it is available, nonoperative portal decompression by transjugular intrahepatic portosystemic shunting (TIPS) is likely to have a further impact. When acute or chronic sclerotherapy fails or when bleeding is secondary to gastric varices or portal hypertensive gastropathy, emergency surgery may be life-saving and should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
4

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 30 publications
0
25
0
4
Order By: Relevance
“…There are only uncontrolled series of TIPS [5,12] and surgical shunts [13] in acute variceal bleeding which do not show clear differences in outcome. Mortality in emergency situations ranges from 20% to 60%, similar in both procedures depending on liver function.…”
Section: Surgical Shunts Vs Tips For Variceal Bleedingmentioning
confidence: 94%
“…There are only uncontrolled series of TIPS [5,12] and surgical shunts [13] in acute variceal bleeding which do not show clear differences in outcome. Mortality in emergency situations ranges from 20% to 60%, similar in both procedures depending on liver function.…”
Section: Surgical Shunts Vs Tips For Variceal Bleedingmentioning
confidence: 94%
“…TIPS require intense post procedure endoscopic surveillance and it is temporary short term measure (34,35) . Esopagogastric devascularisation has prime role in the management of emergency and elective variceal bleeding, it's indication already mentioned in the material and methods (30,36) . Liver transplantation is the curative treatment of chronic liver disease with portal hypertension and related complications (6)(7)(8)(9) .…”
Section: Discussionmentioning
confidence: 99%
“…Bernard B et al and Gu DY et al reported that operative mortality varies between 15-90% depending upon the liver function (51,52) . Hepatic functional reseve is the main determinant of mortality (30,40,53) . In ChildPugh grade A operative mortality rate may be as low as 15%, but in Child-Pugh grade C, it may be as high as 90%.In our studyout of 13 Child C cirrhotic patients, 9 patients died which is 69.23% which is lesser as compared to world literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although emergent surgery is extremely effective in arresting hemorrhage and preventing rebleeding, it is associated with an approximately 50% mortality rate [14,17,18] because many patients die of liver failure and complications of surgery despite achievement of hemostasis. Those patients with severe hemorrhage, tense ascites, deep coma, aspiration pneumonia, renal failure, or sepsis are particularly at risk for dying [17,19,20]. Indeed, it has been recommended that such patients should not undergo surgery [17].…”
Section: Role Of Tips During Active Hemorrhage From Esophageal Varicesmentioning
confidence: 99%